A Comparison Of GDP Growth Of European Countries During 2008-2012 From The Regional And Other Perspectives / Porównanie Wzrostu Pkb W Okresie 2008-2012 W Krajach Europejskich Z Regionalnej I Innej Perspektywy - Mazurek, Jiří (Comparative Economic Research. Central and Eastern Europe, 2015)
The aim of the article is to compare the total real GDP growth of European countries from the 3rd quarter of 2008 with the 3rd quarter of 2012, the period characterized by a predominant economic stagnation or economic recession in the majority of examined European countries. The countries are divided into groups based on the following grounds: whether they are geographically close to the economic center (Germany) or peripheral, whether they are in the eurozone or not, whether they are (new) EU members or ‘old’ ones, etc. The main findings from the comparisons are as follows: 1. European countries close to the economic center (Germany and its neighbours) experienced, on average, positive economic growth during examined period, while countries from European periphery on average experienced negative economic growth during the same period. This difference was found statistically significant at the α = 0.01 level. 2. Differences between eurozone and non-eurozone, old and new EU members, and between more and less populated countries were found statistically insignificant. 3. European regions with the most negative real total GDP growth included the Baltics, the Balkans, Southern Europe (Italy, Portugal) and Iceland. The most successful countries with the most positive real total GDP growth were central European countries (Poland, Slovakia, Germany, Switzerland, Austria) and those in northern Europe (Sweden and Norway). Celem artykułu jest porównanie całkowitego wzrostu realnego PKB w krajach europejskich od III kwartału 2008 roku do III kwartału 2012 roku, w okresie charakteryzującym się przewagą stagnacji i recesji gospodarczej, która miała miejsce w większości badanych krajów europejskich. Kraje zostały podzielone na grupy na podstawie następujących kryteriów: geograficzna bliskość lub peryferyjność w stosunku do centrum gospodarczego (Niemcy), członkostwo w strefie euro lub jego brak, członkostwo w UE (z podziałem na kraje starej i nowej Unii) lub jego brak. Główne wnioski z porównania są następujące: 1. Kraje ...